Temporal fluctuation and reproduction of Thermocyclops decipiens (Copepoda, Cyclopoida) in an eutrophic lake of central Brazil - Padovesi-Fonseca, Claudia (Universidad de Costa Rica, 2002)
Lake Paranoá is an eutrophic reservoir situated in the urban region of Brasília. This study was carried out in a fixed collection station located in the Riacho Fundo branch of the reservoir. Zooplankton samples were collected at intervals of 3-5 d at 9:00 a.m. during two months in the dry and rainy seasons for two years (dry- 1996, rainy-1997, dry-1997 and rainy-1998), using a 64 μm-mesh plankton net. The most predominant species was Thermocyclops decipiens (about 50% of the total zooplankton community), which during the whole period had a high reproductive rate. The highest densities were found in the dry-1996 season (1700 ind/l for nauplii), and also fluctuated widely overtime. Nauplii stages dominated during the four periods, comprising 50-75% of the total population density. Ovigerous females peaked in the dry-1996 and rainy-1997 seasons, with 20-30% of the total females. The largest peak in egg production occurred during the dry-1996 season, and the total egg production was 2.0x103 eggs/l. Mesocyclops longisetus is a first record for Lake Paranoá. The ecological factors that determine the success of T. decipiens in eutrophic systems are related to omnivorous feeding habits and prey-predator interactions.